1998
DOI: 10.1111/j.1095-8649.1998.tb00807.x
|View full text |Cite
|
Sign up to set email alerts
|

Do the habitats, mouth morphology and diets of the mullids Upeneichthys stotti and U. lineatus in coastal waters of south‐western Australia differ?

Abstract: Two benthic carnivorous goatfish (Mullidae), Upeneichthys stotti (max total length, L T =179 mm) and U. lineatus (max L T =257 mm), were trawled from the inner continental shelf waters of Western Australia. U. stotti was found almost exclusively offshore at 20-35 m depth, while U. lineatus was most abundant inshore at 5-15 m depth. Smaller individuals of both species ate small, thin-shelled mysids, tanaids and amphipods, while larger fish ate large, hard-bodied isopods, carid decapods and brachyuran crabs. Cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
1
2

Year Published

1998
1998
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 48 publications
3
40
1
2
Order By: Relevance
“…A number of studies on goatfish diets are reported from the Pacific (Sorden 1982, Lukoschek & McCormick 2001, Sampey et al 2007), the tropical West Atlantic (Munro 1976, Humann & DeLoach 2002, the Mediterranean and the Red Sea (Ben-Eliahu & Golani 1990, Golani & Galil 1991, Wahbeh 1992. Published data from the Indian Ocean are scarce and concern only the genus Upeneichthys (Platell et al 1998). Sympatric mullid species can greatly differ in their depth distribution, foraging substratum selection and feeding modes (Gosline 1984, McCormick 1995, Platell et al 1998.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies on goatfish diets are reported from the Pacific (Sorden 1982, Lukoschek & McCormick 2001, Sampey et al 2007), the tropical West Atlantic (Munro 1976, Humann & DeLoach 2002, the Mediterranean and the Red Sea (Ben-Eliahu & Golani 1990, Golani & Galil 1991, Wahbeh 1992. Published data from the Indian Ocean are scarce and concern only the genus Upeneichthys (Platell et al 1998). Sympatric mullid species can greatly differ in their depth distribution, foraging substratum selection and feeding modes (Gosline 1984, McCormick 1995, Platell et al 1998.…”
Section: Introductionmentioning
confidence: 99%
“…Peixes bentívoros apresentam uma grande diversidade de comportamentos alimentares (Gerking 1994), além de várias adaptações morfológicas relativas ao comportamento de forrageamento e fuga de predadores, e exploram de forma eficiente os substratos bentônicos consolidados e não consolidados (Hobson & Chess 1986, McCornick 1995, Platell et al 1998. Esses peixes possuem usualmente apêndices sensoriais e maxilares inferiores móveis, predando invertebrados bentônicos associados ao fundo, enterrando a boca no substrato e engolindo parte do sedimento (Hobson & Chess 1986, Sazima 1986, Edgar & Shaw 1995.…”
Section: Introductionunclassified
“…Mulloidichthys dentatus (Gill, 1862) Parupeneus insularis Randall & Myers, 2002 Depth-related habitat segregation has also been observed in another species pair, the blue-lined goatfish, Upeneichthys lineatus, and U. stotti (Platell et al 1998). There are also species differences in substrate preferences and in the flexibility of using alternative habitat types (McCormick 1995;.…”
Section: Natural Habitatmentioning
confidence: 99%
“…However, many other morphological traits of goatfishes, such as body size, coloration, head form, otolith form, or the number of countable characters, such as gillrakers, fin rays, or vertebrae, may vary interspecifically (e.g. Lachner 1954;Thomas 1969;Platell et al 1998;Uiblein et al 1998;Aguirre & Lombarte 1999;Kim 2002;Randall 2004) or intraspecifically (e.g. Fage 1909;Rosenblatt & Hoese 1968;Aguirre 1997;McCormick 1993McCormick , 1995Mamuris et al 1998;Uiblein et al 1998;Mahé et al 2005;Pothin et al 2006;Sabatini 2007).…”
Section: Goatfish Systematics and Taxonomymentioning
confidence: 99%
See 1 more Smart Citation